DECISION ANALYSIS FOR RESERVOIR PRESSURE DEPLETION IN LOW QUALITY SAND RESERVOIR OF HEAVY OIL WELL AT PT. CENTRAL DINAMIKA ENERGI (CDE)* - Saleh, Rahmat
Central Dinamika Energi (CDE)* is multinational oil and gas company which has been operating in Indonesia for more than 90 years. The company has been giving the significant contribution to the economic growth by creating lots of job opportunity as well as delivering nearly 30% of total country’s daily oil production. CDE will hand over its Production Sharing Contract (PSC) concession area to the Government of Indonesia (GOI) in August 2021. Despite that, CDE is expected to start drilling program to maintain the oil production and flatten the oil production declining curve.